A systematic review and meta-analysis of acupuncture treatment for oral ulcer. Issue 29 (17th July 2020) - Yan, Hang; Jin, Zhao; Jin, Wenqin; Zhong, Yanmei; Ai, Huangping; Wu, Yeke; Xu, Qianrong; Bai, Xiaoyan; Liu, Donghao; Nie, Wenhan; Zuo, Yuling
Abstract: Background: Oral ulcers (OU) is a common oral mucosal disease manifested with obvious pain; in some studies, the efficacy of acupuncture in OU has been confirmed, but the systematic reviews and meta-analyses for them are lacking. Our aim is to evaluate the efficacy and safety of acupuncture in the treatment of OU. Methods: Relevant randomized controlled trials (RCTs), quasi RCTs and non-RCTs will be identified by systematic searching from the following electronic databases: PubMed, Embase, the Cochrane Library, Chinese Biomedical Literature Database, China National Knowledge Infrastructure, China Science and Technology Journal database, and Wanfang Data (since inception of the databases to present). In addition, ongoing trials will be retrieved from the Chinese Clinical Trial Register, World Health Organization International Clinical Trials Registry Platform, Clinical Trials, and The Clinical Trials Register. Grey literature will be also taken into consideration, including academic dissertation, minutes of the meeting from Chinese Biomedical Literature Database, China National Knowledge Infrastructure, China Science and Technology Journal database, and Wanfang Data. There are no language restrictions. Results: Ethical approval is not required because this study is based on published papers. After peer-review, the study will be disseminated in scientific journals and conferences. Conclusion: This systematic review will provide evidence for the efficacy and safety of acupuncture for Oral ulcers. Trial registration number: CRD42020144911.